Response Surface Based Optimization of Thermal Stability of Nano Composite PA6/MMT/MH - Hezari, M.; Yazdanshenas, M.E. (Asian Journal of Chemistry, 2011)
The thermal stability properties of polyamide nano composites (nylon 6/montmorillonite/magnesium hydroxide) were investigated using differential scanning calorimetry, thermogravimetric analysis. In order to study the morphological structure of the materials by TEM, XRD and FTIR analysis were also carried out. The nano composites were prepared using the melt mixing technique in twin screw extruder. Particular attention was given to studying the influence of different processing condition (barrel temperature profile and screw rate) and compositions of PA6, nano clay and nano magnesium hydrate blends. The results show that all the properties analysis were strongly influenced by the nano composite composition, instead of processing conditions. Using response surface system optimal mathematical models to determine and quantify the relation between values and to find out the setting of experimental factors that produce the best value or the best set of values of the response.